(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
People communicate with each other using verbal structural codes that, in their linguistic context, turn into semantic carriers. These carriers highlight the importance of the structure in suggesting meaning, to form the general connotation that the creator sends to the recipient. The context works to accumulate suggestive energy whose goal is to influence the recipient, and to convey the intended meanings to him through a linguistic message that the poet is interested in organizing in different contexts, but these moral and linguistic contexts complement each other to reach the stages of effectiveness in displacing the absurdity of interpretation, and for the message to reach the addressee safely. Researchers have discussed the context extensively, highlighting the importance of this context and its role in revealing the meaning. We find it to be the context of a maqam and an article, and the two previous contexts combine to reach a semantic structure governed by a number of semantic relationships for words within their linguistic field around which they are centered with their counterparts in the same context. The context highlights the intended meaning of the textual discourse, and highlights the linguistic stock that is filled with many vocabulary owned by the creator. The context goes beyond this stock to reach the stage of influencing its recipients, especially when the context of the word gives multiple different meanings from one context to another, and Omar Abu Risha is one of the creators whose objectivity and subjectivity have merged. In the duality of (the position, the article), to reveal a human experience To present it, he used the ability of the creative context to give the meaning he wanted.